The Current State ofthe Individual: A Meditation on - Boutin, Maurice (Toronto journal of theology, 2007)
Richard Drew's photo, taken on September 11,2001, was published in a few newspapers on September 12 (see http://wtc10048nyc.free.fr/071.htrnl). It shows a man who jumped from a window of the restaurant Window to the World and is in free fall alongside one of the twin towers of the World Trade Center. Because the picture was deemed too violent by a good number of newspaper readers, it quickly disappeared from the material used in reports on the disastrous event in New York City. And yet the photo, simply entitled The Falling Man, offers the opportunity to restart both anamnesis and critical distanciation instead of needless contemplation of building debris.